A non-canonical melanin biosynthesis pathway protects Aspergillus terreus conidia from environmental stress - Geib, Elena; Gressler, Markus; Viediernikova, Iuliia; Hillmann, Falk; Jacobsen, Ilse D.; Nietzsche, Sandor; Hertweck, Christian; Brock, Matthias (Elsevier, 2016)
Pro- and eukaryotes produce melanin for protection from environmental stress or as virulence determinant. The human pathogenic fungus Aspergillus fumigatus and related Ascomycetes produce dihydroxynaphthalene (DHN) melanin in conidia, which is essential for inhibiting phagolysosome acidification. In contrast, Aspergillus terreus lacks genes for biosynthesis of DHN-melanin. Therefore, the origin of the pigment in A. terreus conidia was elucidated. Expression analyses from conidiation conditions identified genes coding for an unusual NRPS-like enzyme (MelA) and a tyrosinase. MelA produces aspulvinone E as precursor, which is activated for polymerisation by the tyrosinase TyrP as shown by heterologous in vivo and in vitro reconstitution of pigment formation. Functional studies revealed that the pigment confers resistance against UV-light and hampers phagocytosis by soil amoeba, but does not inhibit acidification of phagolysosomes. Since A. terreus conidia prefer persistence at acidic pH, this uncommon type of melanin, termed Asp-melanin, might specifically contribute to survival in the environment.